Increased Levels of Circulating Glial Fibrillary Acidic Protein and Collapsin Response Mediator Protein-2 Autoantibodies in the Acute Stage of Spinal Cord Injury Predict the Subsequent Development of Neuropathic Pain - Hergenroeder, Georgene W; Redell, John B; Choi, H Alex; Schmitt, Lisa; Donovan, William; Francisco, Gerard E; Schmitt, Karl; Moore, Anthony N; Dash, Pramod K (Journal of neurotrauma, 2018)
Neuropathic pain develops in 40-70% of spinal cord injury (SCI) patients and markedly compromises quality of life. We examined plasma from SCI patients for autoantibodies to glial fibrillary acidic protein (GFAP) and collapsin response mediator protein-2 (CRMP2) and evaluated their relationship to the development of neuropathic pain. In study 1, plasma samples and clinical data from 80 chronic SCI patients (1-41 years post-SCI) were collected and screened for GFAP autoantibodies (GFAPab). Results from study 1 indicated that GFAPab were present in 34 of 80 (42.5%) patients, but circulating levels did not correlate with the occurrence of neuropathic pain. In study 2, longitudinal plasma samples and clinical data were collected from 38 acute SCI patients. The level of GFAPab measured at 16 ± 7 days post-SCI was found to be significantly higher in patients that subsequently developed neuropathic pain (within 6 months post-SCI) than patients who did not (T = 219; p = 0.02). In study 3, we identified CRMP2 as an autoantibody target (CRMP2ab) in 23% of acute SCI patients. The presence of GFAPab and/or CRMP2ab increased the odds of subsequently developing neuropathic pain within 6 months of injury by 9.5 times (p = 0.006). Our results suggest that if a causal link can be established between these autoantibodies and the development of neuropathic pain, strategies aimed at reducing the circulating levels of these autoantibodies may have therapeutic value.